Instability of residences founded on volcanic cohesive soils during the 2016 Kumamoto Earthquake - K. Yasuhara; H. Watanabe; K. Kobayashi; M. Yoshimi; Y. Arai; S. Hosoya; M.S. Tajiri; S. Murakami (Lowland Technology International, 2017)
This paper is intended to describe that the nonlinearity of seismic response for soft deposits is associated with the cyclic degradation of strength and stiffness in shallow deposits of cohesive volcanic ash soils, which caused devastation to residences. Using the simplified methodologies proposed previously by the authors, which incorporate cyclic strength and stiffness degradation characteristics of saturated cohesive soils, prediction was conducted for residential settlement and lateral deformation of residences with retaining walls founded on and against a shallow layer of cohesive volcanic ash soils. A chart for construction management incorporating the results in terms of earthquake-induced settlement vs. lateral deformationsettlement relations predicted the use of the methodology described above. Results suggest that residences are likely to sustain severe damage when the normalized excess pore pressures generated during the earthquake extend to about 0.7. Results also show that damage to retaining walls was also associated with earthquake-induced strength degradation of backfill soils.